Naturally Occurring Compounds With Larvicidal Activity Against Malaria Mosquitoes - Milugo, Trizah K.; Tchouassi, David P.; Kavishe, Reginald A.; Dinglasan, Rhoel R.; Torto, Baldwyn (Frontiers in Tropical Diseases, 2021)
Female Anopheles mosquitoes transmit Plasmodium parasites that cause human malaria. Currently, vector control is the most widely deployed approach to reduce mosquito population and hence disease transmission. This relies on use of insecticide-based interventions including Long-lasting Insecticide-treated Nets (LLINs) and Indoor Residual Spraying (IRS) where scale-up has contributed to a dramatic decline in malaria deaths and morbidity over the past decade. Challenges to their effective use include the emergence and spread of insecticide resistance by malaria vector populations coupled with the inability to curb outdoor transmission. Under these situations, use of larvicides through larval source management (LSM) can complement these existing measures. The need to minimize environmental impact and effect on non-target organisms has spurred interest in the development of eco-friendly larvicides of natural origin. Here, we review literature published in the last five years to highlight compounds of natural origin found to exhibit larvicidal activity against malaria mosquitoes. Specifically, the larvicidal activity of different classes of compounds is discussed including their effect on non-target organisms. Additionally, we provide suggestions for future research into mosquito larvicides including the use of chemical synthesis to improve the bioactivity of known natural compounds.